(3Yde ebGUO GdTGQY (B/s - (3GdQHjYI, YHO GdYRjR Hf YHO GdQMef Hf Ydjs 1361 (3gLQj(B-s ((3GdQjGV (B- (3GdeedcI GdYQHjI GdSYhOjI (B:s (3GdYHjcGf ddfTQ hGdJhRjY ,s, 2019)
(3jJfGdh cJGH (B((3Yde ebGUO GdTGQY(B) (3hGdPj bGe HJCdjag (B((3YHO GdYRjR Hf YHO GdQMef Hf Ydj Hf QHjYI(B) (3aj (B(372 (3UaMI(B) (3ef GdbWY GdeJhSW, ehVhY (B((3CUhd Gdabg GdESdGej(B) (3eSJYQVG GdCJj (B: (3ebGUO GdTGQY gj SQ GdJTQjY, heYQaJgG gj eYQaI SQ GdJTQjY, hJHOh CgejJgG ef MjK Ef HgG jYQa GSJfHGW GdCMcGe GdTQYjI, hHgG jhba Ydi GdeUGdM GdJj bUOgG GdTGQY GdMcje ef JTQjYg ddCMcGe(B. s
(3Ef ebGUO GdTGQY gj SQ GdJTQjY(B, (3heYQaJgG gj eYQaI SQ GdJTQjY(B.s
(3HHdjhLQGajI (B: (3UaMI (B345-356.s
Keywords: (3CUhd Gdabg GdESdGejs; (3ebGUO GdTQjYIs